Production technology for organic coleus - Atul Jayapal (Department of Agronomy, College of Agriculture, 2012)
An investigation entitled “Production technology for organic coleus” was undertaken at College of Agriculture, Vellayani from August to December 2011 to standardize an organic nutrient package for coleus and work out the economics of cultivation. The treatments consisted of factorial combinations of three levels of organic manure (to supply100%, 75% and 50% recommended dose of 60:60:100 kg NPK ha-1), two levels of biofertilizer (with PGPR mix 1 and without biofertilizer) and two varieties (Sree Dhara and Suphala). The trial was laid out in 3 x 2 x 2 asymmetrical factorial RBD with three replications. Neem cake @ 1 t ha-1 was applied uniformly to all the plots. Growth characters like plant height and number of branches per plant were not significantly influenced by different levels of organic manure or biofertilizer application. But levels of organic manure exerted significant influence on leaf number and LAI during early and later stages of crop growth. During the initial stage, 100% and 75% levels of organic manure were on par in their effects on leaf number and LAI but during later stage of the crop, 100% level was superior to other levels. Application of PGPR mix 1 produced higher LAI during initial and final stages of the crop. The var. Sree Dhara produced taller plants with more number of branches during later stages of growth. But the var. Suphala produced higher leaf number and LAI during the initial stage while the var. Sree Dhara dominated at other stages of growth. Yield components like number of tubers and marketable tubers per plant were influenced by levels of organic manure but the effects of 100% and 75% levels were on par. But an increasing trend in the weight of tubers and marketable tubers per plant was observed with increase in the level of organic manure. Application of PGPR mix 1 exerted profound influence on these yield components. The var. Sree Dhara dominated over the var. Suphala in these yield components but the var. Suphala recorded significantly higher percentage number of marketable tubers per plant. Tuber yield showed an increasing trend with incremental doses of organic manure recording the highest yield with 100% level. Application of PGPR mix 1 improved the yield. The var. Sree Dhara produced higher yield than the var. Suphala. Dry matter production and utilization index increased with increase in the level of organic manure and also due to application of PGPR mix 1. The var. Sree Dhara was found superior in dry matter production. Quality characters of tuber such as starch and protein contents were not influenced by the treatments. The tubers could be stored for one month without sprouting, microbial decay and appreciable physiological loss in weight. Increasing levels of organic manure significantly increased the uptake of P and K but failed to produce significant effect on N uptake. Application of PGPR mix 1 enhanced the nutrient uptake. The var. Sree Dhara registered higher uptake of nutrients than the var. Suphala. Soil nutrient status after the experiment in terms of organic carbon and available P and K contents increased with increase in the level of organic manure. Application of PGPR mix 1 improved the status of available P and K in soil. Available N in the soil was not influenced by the treatments. There was no significant difference in nutrient status of the soil after the experiment due to varieties. Higher net income and BCR could be obtained by the application of 100% or 75% levels of organic manure. Application of PGPR mix 1 increased the net income. The var. Sree Dhara recorded higher net income and BCR than the var. Suphala. The study revealed that coleus has great potential for organic cultivation. Application of 100% RD of NPK (60:60:100 kg ha-1) through organic manures (6t FYM + 3t CPC + 3 t wood ash ha-1) along with PGPR mix 1 and the recommended basal dose of FYM @ 10 t ha-1 is necessary for getting higher yields of organic coleus. During the normal planting season, var. Sree Dhara produced higher yields, net income & BCR than the var. Suphala. But the var. Suphala which is recommended for year round cultivation is found to be early maturing than the var. Sree Dhara.